2020
DOI: 10.3390/ijerph17051626
|View full text |Cite
|
Sign up to set email alerts
|

The Theory of Planned Behaviour in Medical Tourism: International Comparison in the Young Consumer Segment

Abstract: The Theory of Planned Behaviour (TPB) assumes the possibility of predicting and explaining humans’ behaviour by identifying their intentions. The intentions are shaped by three groups of factors: attitudes towards, social norms and perceived behavioural control over the behaviour. The aim of the research is to examine the applicability of the TPB in medical tourism and to check whether there are differences in predicting the intentions of medical tourists from different countries. The study covered potential m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 65 publications
1
21
0
6
Order By: Relevance
“…TRA posits that behavioral intent is the most relevant predictor of person's behavior, while attitudes towards outcome and subjective social norm act as antecedents of behavioral intention [59]. TPB is an extended approach of TRA and tries to explain behavioral intentions through three groups of antecedents: attitudes, social norms and perceived behavioral control over behavior [60,61]. There are also models which attempt to explain tourist behavior through satisfaction which consists of image, attitude and motivation [31].…”
Section: Attitudes Behavior and The Environmentmentioning
confidence: 99%
“…TRA posits that behavioral intent is the most relevant predictor of person's behavior, while attitudes towards outcome and subjective social norm act as antecedents of behavioral intention [59]. TPB is an extended approach of TRA and tries to explain behavioral intentions through three groups of antecedents: attitudes, social norms and perceived behavioral control over behavior [60,61]. There are also models which attempt to explain tourist behavior through satisfaction which consists of image, attitude and motivation [31].…”
Section: Attitudes Behavior and The Environmentmentioning
confidence: 99%
“…The health belief model includes perceptions of risk, severity, benefits, and barriers and emphasizes the individual's own perceptions and beliefs while ignoring the influence of external pressures such as subjective norms [ 18 ]. The theory of planned behavior emphasizes that behavioral attitudes, subjective norms, and perceived behavioral control predict behavioral intentions and behavior but, to some extent, ignores the influence of emotional feelings such as threat and fear on behavior [ 19 , 20 ]. It follows that a single behavior change theory can only analyze and predict behavior from one perspective, leading to shortcomings in its explanation of behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Theory of planned behavior and its extensions are often used to illustrate the mechanism behind tourists’ behavior intentions, and exhibit good explanatory and predictive power. Boguszewicz-Kreft et al (2020) have verified the TPB model’s applicability to medical tourism and compared the differential willingness among consumers of different nationalities to use medical tourism services. Hu et al (2021) have found that attitudes, perceived behavioral control, environmental awareness, and perceived moral obligations are significantly and positively correlated with young people’s intent for low-carbon travel behavior, while subjective norms are not.…”
Section: Theoretical Background and Hypothetical Developmentmentioning
confidence: 93%